The Existence and Significance of Dayah as a Traditional Islamic Educational Institution in Indonesia Based on Local Wisdom - Zulkifli Abdurrahman Usman; Bachtiar Akob; Usman Usman; Asnawi Asnawi; Nauwal Aufa (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
The historical formation of Islamic traditional institutions in Aceh, particularly dayah, remains underexplored, especially regarding the relationship between their socio-historical origins and foundational educational practices. This study aims to analyze the historical establishment and basic education model of Dayah Raudhatul Huda. Using a qualitative descriptive design with socio-historical and Islamic education approaches, data were collected through in-depth interviews with dayah leaders and supported by document analysis. The findings indicate that the institution emerged through strong community participation, driven by religious consciousness, waqf contributions, and the need for accessible Islamic education. Its educational model reflects the salafiyah tradition at the ula and wustha levels, focusing on classical Islamic texts while integrating faith, ritual practice, and moral discipline as core elements of student formation. These findings highlight that the sustainability of dayah lies in its community-based foundation and value-oriented pedagogy. The study implies that such a model offers a relevant framework for strengthening character education and religious literacy in contemporary Islamic education systems.